Delayed Collapse of the North Pacific Intermediate Water After the Glacial Termination. Issue 13 (9th July 2021) - Zhao, Debo; Wan, Shiming; Lu, Zhengyao; Zhai, Lina; Feng, Xuguang; Shi, Xuefa; Li, Anchun
Abstract: Carbon release from the North Pacific in glacial‐interglacial cycles has been mainly linked to the North Pacific Intermediate Water (NPIW) formation and associated carbon/nutrient water upwelling and biological productivity changes. However, relationship between NPIW and atmospheric CO2 change in the early interglacial remains unclear. Here we report a high‐resolution sediment record of NPIW evolution based on paleo‐redox changes in the Western North Pacific during the last 400 ka. Our proxy and model results reveal a delayed collapse of NPIW after the glacial termination was coeval with decreased salinity of intermediate water and increased net rainfall in the North Pacific. Such weakened NPIW formation in the North Pacific probably make a contribution to maintain high atmospheric CO2 concentrations through weakened intermediate‐to‐deep ocean stratification and reduced subsurface biological pump net efficiency, countering the return to more stratified conditions in the Southern Ocean, which should drive down atmospheric CO2 during the early interglacial. Plain Language Summary: The high‐latitude North Pacific is an important region where ocean interacts with the atmospheric carbon cycle. CO2 outgassing from the interior ocean of North Pacific to the surface is mainly controlled by the upwelling as well as the biological productivity determined by the NPIW formation. Relationship between changes in the NPIW and atmospheric CO2 in the early interglacial remains unclear. Here we reconstructed the NPIW evolution during the last 400 ka, and combined with climate model results, we found a delayed collapse of NPIW compared with the Southern Ocean deglacial warming, which was synchronous with the decreased seawater salinity in response to increased net rainfall in the North Pacific. This NPIW collapse after glacial termination should weaken the intermediate‐to‐deep ocean stratification, and thus favored the upwelling of nutrient/carbon‐rich deep water to the surface. Besides, combined with the decreased nutrient‐poor subtropical waters supply from the weakened Pacific meridional overturning circulation, the biological pump net efficiency was reduced and thus consumed less CO2 . These would counter the return to more stratified conditions in the Southern Ocean, which should drive down atmospheric CO2 during the early interglacial, and thus probably make a contribution to maintain high atmospheric CO2 concentration during the early interglacial. Key Points: NPIW evolution during the last 400 ka was reconstructed based on the paleo‐redox changes in the northern Okinawa Trough Precessional changes of NPIW formation were mainly forced by the net rainfall in the North Pacific Delayed collapse of NPIW probably contributed to maintain high atmospheric CO2 concentrations during the early interglacial